2015
DOI: 10.1186/s12348-015-0063-y
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous endophthalmitis: diagnosis, management, and prognosis

Abstract: Endogenous endophthalmitis is an ophthalmic emergency that can have severe sight-threatening complications. It is often a diagnostic challenge because it can manifest at any age and is associated with a number of underlying predisposing factors. Microorganisms associated with this condition vary along a broad spectrum. Depending upon the severity of the disease, both medical and surgical interventions may be employed. Due to rarity of the disease, there are no guidelines in literature for optimal management of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
153
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(162 citation statements)
references
References 94 publications
(171 reference statements)
2
153
2
5
Order By: Relevance
“…Despite the severity of the condition the diagnosis is often delayed, with a mean delay of 3.2 days 1. Delay in diagnosis, as was the case with the above patient, is a poor prognostic indicator 2. Other poor prognostic indicators include poor initial visual acuity, centrally located lesions, presence of a hypopyon, and rapid onset of symptoms, unilateral involvement and panophthalmitis.…”
Section: Descriptionmentioning
confidence: 76%
See 1 more Smart Citation
“…Despite the severity of the condition the diagnosis is often delayed, with a mean delay of 3.2 days 1. Delay in diagnosis, as was the case with the above patient, is a poor prognostic indicator 2. Other poor prognostic indicators include poor initial visual acuity, centrally located lesions, presence of a hypopyon, and rapid onset of symptoms, unilateral involvement and panophthalmitis.…”
Section: Descriptionmentioning
confidence: 76%
“…Risk factors for the development of EBE include hospitalisation, diabetes, immunosuppression, urinary tract infection, neutropenia, HIV, intravenous drug use and indwelling catheters 2. It has been suggested that diabetes induces increased blood-retinal barrier permeability and subsequent risk of development of EBE 3…”
Section: Descriptionmentioning
confidence: 99%
“…pneumoniae infections, having only been described in isolated case reports [14]. Endogenous endophthalmitis occurs when bacteria reach the eye via bloodstream infection or through central nervous infection spread via the optic nerve [15, 16]. It is often associated with chronic predisposing conditions such as those that cause a baseline immunodeficient state (i.e., diabetes mellitus, HIV, and ESRD).…”
Section: Discussionmentioning
confidence: 99%
“…Fungal infections have also been implicated quite often. The right eye is more often affected than the left due to a more direct route through the right carotid artery [12, 16]. Diagnosis is made with high clinical suspicion in the setting of other risk factors such as systemic infection and imaging concerning for intraocular infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation